First insight into oral health misinformation in Jordan; an analysis of web content and information-seeking behaviors - Issam B. Rasheed; Bayan F. Ababneh; Yara I. Al-Habsheh (PLoS ONE, 2025)
Background Integrating the internet into daily life has profoundly influenced the public's behavior of seeking health information. Free access to cyberspace created a fertile environment for the spread of oral health misinformation, which can have a detrimental impact on the public’s oral health. The prevalence of oral health misinformation in Jordan has not been investigated; therefore, it is crucial to understand how oral health misinformation originates and what contributes to its dissemination. Objectives This study aims to examine the prevalence of oral health misinformation published on web pages in Jordan and to offer insight into the public's information-seeking behaviors regarding oral health. Methods This study is a mixed methods infodemiological analysis of oral health misinformation. A systematic content analysis was executed on web pages published in the Arabic language in Jordan from 2019 to 2023. Results 704 web pages were retrieved, of which 320 relevant web pages were included in the content analysis. Among these, 193 web pages (60.3%) published oral health misinformation. Publishers without a professional background published 185 web pages (95.9%) of the total misinformation-expressing web pages. According to the dental field, the highest frequency of misinformation occurred in oral medicine-101 web pages (52.3%). The validity of published oral health information was significantly influenced by the publishers’ interest (P = 0.006), the articles’ main themes (P = 0.005), and the publishers' professional background (P < 0.001). Contextual analysis of oral health misinformation showed significant differences among dental fields (P = 0.019), with the most frequent occurences related to causes (18.8%), home remedies (15.7%), and treatment (15.5%). Geographical variations in interest in oral health searches were observed across Jordanian governorates (P < 0.001), and temporal trends in interest varied significantly across the five-year period(P = 0.019). Conclusion The findings of this study suggest a need for public health interventions to restrict the dissemination of oral health misinformation.